RELEVANSI AL-KHILAF AL-FIQHI DAN TOLERANSI (Analisis Toleransi Antar Umat Islam Dalam Fiqh) - M Ridwan Hasbi (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2011)
Meaning say 'ikhtilaf' and 'khilaf' be as and mutually neighboring, so fathoms a meanning,is distinctive clear a root, opinion or method that variably an one by another one. Tolerance in trouble that diperselisihkan can be done if we are not fanatical to one opinion that go againts to have Say the other. Its principle; shall respect others opinion and realises its medley possible level with another. Shall be realished that al-khilaf al-fiqhi tem of nash's grasp and gets effort for its application in human benefit